Postur Kerja dan Risiko Low Back Pain pada Pekerja Pasiran - Nurkertamanda, Denny; Adiputra, I Nyoman; Tirtayasa, Ketut; Adiatmika, I Putu Gede (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 3 No 2 (2017): Volume 3 No 2 Desember 2017DO - 10.24843/JEI.2017.v03.i02.p02, 2017)
One of the manual matrial handling jobs is the derivative work from the top of the truck. In working the workers use a tool that enggrong which is a short-handed shovel. Due to the use of employee enggrong work with stooped posture. This work posture raises the potential for low back pain in workers. This study is a cross sectional study with a sample of 9 participants. The purpose of research is to find potential risks of low back pain based on angle trunk when workers work sent down the sand by enggrong. Angle trunk which is predicted covering: 1 angle trunk flexion, 2) angle trunk bending, and 3) angle trunk twisting. Work posture data was taken using Microsoft Kinect TM 3D camera and analyzed by using Siemen Jack 3D Static Strength Prediction Program (3DSSPP) software to predict angle trunk. The result of the analysis of the 6 work postures showed that worker's frequently employed posture had the average angle trunk flexion of 61.1 0 ± 10.09 0 , angle trunk bending of 19.8 0 ± 6.74 0 and angle trunk twisting of 20.0 0 ± 9.03 0 . The average angle trunk flexion at 87.28% of maximal angle is a major cause risk low back pain. So that it can be summed up the potential for low back pain on sand workers. Intervention ergonomics need to prevent and reduce potential risks happened low back pain on sand workers.